Impact of Hydrothermal Treatments on Nutritional Value and Mineral Bioaccessibility of Brussels Sprouts (Brassica oleracea var. gemmifera) - Joanna Doniec; Adam Florkiewicz; Robert Duliński; Agnieszka Filipiak-Florkiewicz (Molecules, 2022)
Hydrothermal treatment of Brussels sprouts (Brassica oleracea var. gemmifera) induces both physical and chemical changes in nutrients and non-nutrients. It also affects the bioaccessibility of individual compounds. The aim of this study was to investigate the influence of hydrothermal treatment (boiling, steaming, and sous vide technique) on the concentration of the selected nutrients and non-nutrients in Brussels sprouts and in vitro bioaccessibility of the mineral components. It has been shown that, in terms of the leaching of nutrients and non-nutrients into the aqueous medium, traditional cooking in water involves the greatest percentage loss (the highest decrease in dry matter (11.8%), ash (13.3%), protein (10.4%), crude fat (43.3%), dietary fiber (9.5%), digestible carbohydrates (12.2%), and most of mineral components (7.6–39.8%)). In contrast, steam cooking and sous vide cooking of Brussels sprouts allow a higher level of preservation of the individual compounds. By using reduced process temperatures and vacuum packaging, sous vide cooking can be an alternative to traditional cooking to preserve the higher nutritional value of Brassica oleracea var. gemmifera (preservation of dry matter, ash, crude fat, and most of the mineral components at the level of the raw sample p ≤ 0.05).